PERANCANGAN PENJADWALAN PRODUKSI DI PERUSAHAAN BORDIR HOKKIMAN SURABAYA - Albert Ong; Linda Herawati Gunawan; Dina Natalia Prayogo (CALYPTRA, 2017)
Abstract Hokkiman is a company which is excel at embroidery based production. Current issues faced by company are unknown standard time for the whole production processes, including machining time for various embroidery’s motives, which result in difficulties of calculating final completion time for an order, and necessity to improve current production scheduling system. The purposes of the research are to determine standard time for every production process, improving production scheduling performance by designing an appropriate production scheduling system that allow the company to accept order with due date requirement. Standard time are obtained by collecting primary datas on the production floor using continuous timing method, followed by the calculation for every production process. Standard time calculation for machining are achieved by using simple linear regression analysis. The new production scheduling system is designed by analyzing current system’s weaknesses. Proposed production scheduling system are made based on the Shortest Processing Time (SPT) method. Results of the research are as following, the improvement of production scheduling performances which are shortened response time (21,61%), makespan can be reduced by 19,17%, faster mean flowtime (21,47%), within the condition of 14 days due date is applied, the amount of job tardiness and lateness are decreased by 5,88% and 21,32% sequentially. Keywords: Standard time, Production Scheduling, Embroidery, Shortest Processing Time, Flowtime Abstrak Hokkiman merupakan perusahaan yang bergerak dalam bidang jasa bordir. Masalah yang dihadapi adalah tidak diketahuinya waktu baku dalam masingmasing proses produksi dan waktu pemesinan setiap motif, sehingga waktu penyelesaian order sulit dikalkulasi menyebabkan perusahaan tidak dapat menerima order yang memiliki tenggat waktu, serta sistem penjadwalan produksi saat ini yang kurang tepat. Tujuan dalam penelitian ini adalah menentukan waktu baku untuk masing-masing proses produksi dan motif bordir sehingga waktu penyelesaian suatu order dapat dikalkulasi, serta meningkatkan kinerja penjadwalan produksi perusahaan dengan merancang sistem penjadwalan produksi sesuai dengan kondisi perusahaan, sehingga perusahaan dapat menerima order yang memiliki tenggat waktu. Waktu baku didapatkan dengan mengumpulkan data primer di lantai produksi melalui metode continuous timing, dilanjutkan menghitung waktu standar untuk setiap proses produksi, perhitungan waktu standar untuk pemesinan suatu motif dilakukan dengan menggunakan model regresi linier. Perancangan penjadwalan produksi dilakukan dengan menganalisis metode penjadwalan awal. Penjadwalan dengan metode usulan dilakukan dengan metode Shortest Processing Time (SPT). Hasil yang didapatkan adalah adanya peningkatan kinerja sebesar 21,61% pada response time, makespan dipersingkat 19,17%, mean flowtime juga turun sebesar 8,84 hari per order (21,47%). Jika ditetapkan tenggat waktu 14 hari pada setiap order, lama keterlambatan dapat dipangkas 21,32%, dan jumlah order yang terlambat berkurang 5,88%. Kata kunci: Waktu Standar, Penjadwalan Produksi, Bordir, Shortest Processing Time, Flowtime